The Contribution of Large and Small Employers to Job Creation in Times of High and Low Unemployment - Moscarini, Giuseppe; Postel-Vinay, Fabien (American Economic Review, 2012)
We document a negative correlation, at business cycle frequencies, between the net job creation rate of large employers and the level of aggregate unemployment that is much stronger than for small employers. The differential growth rate of employment between initially large and small employers has an unconditional correlation of —0.5 with the unemployment rate, and varies by about 5 percent over the business cycle. We exploit several datasets from the United States, Denmark, and France, both repeated cross sections and job flows with employer longitudinal information, spanning the last four decades and several business cycles. We discuss implications for theories of factor demand. (JEL D22, E23, E32, J23, L25)